Strategi Komunikasi Inovatif dalam Mengeliminasi Tuberkulosis di Wonogiri: Studi Kasus Mentari Sehat Indonesia - Wihastiningrum, Zabrina Damayanti; Kusuma, Arif Surya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study examines communication strategies used in tuberculosis control and increasing treatment compliance in Wonogiri Regency, by highlighting the implementation of community-based health services such as free sputum examination, TB treatment, integrated health post services, patient assistance, and cultural approaches. The communication strategies implemented include door-to-door visits, group communication in integrated health post forums, and local culture-based counseling involving community leaders as trusted communicators. Communication techniques are used to build trust and increase patient involvement in the treatment process. Verzosa's Strategic Communication for Development theory, which emphasizes the importance of systematic communication planning based on community needs. Using a qualitative case study method, data were obtained interviews with purposive sampling and participatory observation, then analyzed using data condensation techniques, data presentation, and drawing/verifying conclusions. Researchers used source triangulation by comparing information from various informants. The results of the study showed that the success elimination program was highly dependent on the active involvement of health cadres, interpersonal communication, and cultural sensitivity in delivering health messages. The implications of this study emphasize the importance of continued cross-level communication and periodic evaluation. Although this program was successful in Wonogiri, its implementation in other areas needs to be adjusted to local demographic and socio-cultural conditions, so further research is needed that covers a wider area for comparative evaluation and formulation of more adaptive health communication strategies.